Modeling the change of land cover and land uses in Khalis district between 1997-2021 and forecasting it up to 2031 using CA-MARCOV - Shahd Ahmed Hassan; Dr. Tanzeeh Majeed Hameed (Migration Letters, 2023)
It is important to know the changes in the land cover and the uses of the land that changed to other uses in a later period, and whether these changes were directed towards an increase or a decrease. Therefore, it was necessary to classify a satellite image for a previous and a later period and to know the changes that occurred in the land cover and the uses of the land through reliance in the classification process on a programmeERDAS IMAGING 14One of the most famous programs used in analyzing and processing visuals, on which the researcher relied on two satellite visualizations Land sat 5-8for my year1997And2021, And To reach an accurate classification of the satellite image have to be processed and improve it, And then cut off The study area from satellite images The two satellite visuals of the aforementioned years were classified into five categories (water, orchards, agricultural fields, barren land, and urbanization). And then it was done Conducting a change detection between the two years to obtain the amount and percentages of change for the types of land cover and land uses for the Khalis district.20.76,26.98%) successively, and this was at the expense of other categories, namely water, orchards, and agricultural fields, which recorded negative change rates that reached () successively between 1997 and 2021. In order to know the behavior of the land cover and land uses within the study area, a simulation was conducted using a modelCA-MARCOVTo predict changes in the land cover and land uses up to the year 2031, and it was found that the urbanization category will continue to expand until its percentage reaches (20.88% after it used to occupy (13.8%) in 1997 and (17.53%) in 2021, and the two categories of water and orchards will continue to decline in their area to reach (0.92, 3.39%), respectively, for each of them, respectively.